PERAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT DALAM PERSPEKTIF HUKUM EKONOMI DAN HUKUM ISLAM - Tarigan, Azhari Akmal (Universitas Medan Area, 2016)
Indonesia wants to achieve political and economic modernization as well as protect people from suffering which arice as a result of the industrialization of life at the same time. One of product legislation that push the economic growth is Law No. 5 of 1999 on Prohibition of Monopolistic Practices and Unfair Business Competition. This law gives equal opportunities to all the people of Indonesia to develop its economic potential. Prohibition monopoly practices and unfair competition is business practices that should be avoided because of the effect it has is quite heavy as not efficiens market, market distortions, which will eventually lead to disserved not only for consumers but also for producers, especially the middle class and small. In turn, the country will also be harmed because it is not supported by a solid economic foundation. Monopoly Practices and unfair competition is contrary to the values of justice and welfare, as an intrinsic human values that can lead to business activities intended to bring prosperity will not materialize at all.